The Fate of Midline Lineages in the Embryos Deficient for Apoptosis in Drosophila melanogaster - Dong, Rong (My University, 1997)
One function of programmed cell death in the developing CNS is the removal of excess cells that provide transient function. Previous studies in Drosophila observed an overpopulation of midline glia cells in embryos deficient for apoptosis. Where do these extra glia cells come from? Using different enhancer traps and antibodies as cell identity markers, the cell number of different CNS midline lineages was assessed in both wild type and Df(3L)H99 embryos which are deficient for apoptosis. The results show that at stage 16 there are approximately 3 cells labeled by midline glia specific markers (AA142 enhancer trap & P[slit1.0/lacZ] reporter construct) in wild type while there are up to 12 cells in embryos deficient for apoptosis. Comparing the number of midline neurons of mutants with that of wild type embryos, there are no detectable changes labeled by the enhancer trap P223, antibody 22C10, or an antibody to Engrailed. Exceptionally, there is one more neuron labeled by enhancer trap XS 5 in Df(3L)H99 embryos. Therefore, apoptosis is restricted to the midline glia lineage. Using P[slit1.0/lacZ] as MG marker, I observed that the extra midline glia in Df(3L)H99 initially appear at late stage 12 or early stage 13. The expression of reaper mRNA precedes programmed cell death. In wild type embryos, the initial expression of reaper mRNA of midline cells is at late stage 11 as revealed by in situ hybridization. These indicate that the first programmed cell death in the midline occurs approximately at stage 12. The supernumerary cells labeled by midline glia specific markers in Df(3L)H99 embryos share featur,es ofthe midline glia. These extra midline glia may be divided into two groups according to their differentiation. The cells of the first group strongly express the AA142 enhancer trap and ensheath the commissures. These cells are functional midline glia corresponding to the surviving midline glia in wild type embryos. The cells of the second group weakly express the AA142 and associate with but do not ensheath the commissures. These are likely the cells which normally undergo apoptosis in wild type. The results of this study indicate that the supernumerary midline glia come from neither midline glia proliferation nor other lineages. They may come from a midline glia progenitor pool in which midline glia marker expression begins at different stages. In wild type embryos, these potential midline glia die by apoptosis before activating midline glia specific genes. In Df(3L)H99 embryos, these midline glia survive and express midline glia markers. All the midline glia die in embryos mutant for spitz group genes. In embryos double mutant for spitz group genes and Df(3L)H99, supernumerary midline glia cells survive. These cells cannot totally rescue the axon tract phenotype of spitz group gene mutants indicating that spitz group genes are necessary for producing 'mature' midline glia. In Df(3L)H99 embryos, approximately 12 midline cells labeled with the midline glia specific marker P[slit1.0/lacZ]. However, there is not a significant increase in the number of midline glia expressingpnt or argos compared with wild type. Therefore, the survival of supernumerary midline glia in embryos deficient for apoptosis does not require DER signaling. However, the DER pathway seems to specify which and how many midline glia progenitors avoid apoptosis.
Midline Lineages in Embryos Deficient for Apoptosis in Drosophila
Keywords: apoptosis; drosophila melanogaster